Analisis Perlindungan Atas Anak Yang Mengalami Kasus Kekerasan Seksual Menurut PandanganHukum Di Indonesia - Farrel Jaluh Arsa Gumay (CV. ITTC INDONESIA, 2024)
In fact, law enforcers provide appropriate sanctions to perpetrators of violence so that the rule of law is truly upheld and social order can be created. It is hoped that this sanction will provide a deterrent effect for perpetrators of sexual violence from repeating their crimes, and because the sanctions given are very severe, it will provide a deterrent effect for other people from committing these crimes. The legal approach is an approach that uses regulations and legislation related to the problems studied, supported by primary and secondary data. The research findings are as follows: Efforts to overcome criminal acts of sexual violence against children among people examined based on the Indonesian Criminal Code show that parents have an important role in protecting children from the threat of sexual violence, participation in the process of handling the sexual violence they experience; his involvement in child involvement cases, both in legal treatment and psychological recovery treatment; and providing psychological services to children and parents. The role of society in overcoming sexual violence against children requires community participation and involvement by paying attention to prevention aspects involving citizens, with the aim of protecting children at the grassroots level. The role of the state, medical rehabilitation is a process of integrated therapeutic action through the restoration of the physical condition of children, child victims and/or witnesses. Rehabilitation is a process of physical, mental and social recovery activities that enable underage victims and underage witnesses to be able to return to carrying out their social functions in social life.